Enhanced visible-light photocatalytic activity of Bi2O2CO3 nanoplates by Fe-doping in the degradation of rhodamine B - Li, Jiahui; Liu, Yuanyuan; Zhou, Yang; Liu, Suqin; Liang, Ying; Luo, Tianxiong; Dai, Gaopeng (Materials research bulletin, 2018)
Fe-doped Bi2O2CO3 nanoplates were developed as visible-light driven photocatalysts with tailorable energy bandgaps. The Fe-doping in Bi2O2CO3 can greatly enhance the photocatalytic degradation of RhB upon visible-light irradiation. [Display omitted] •Fe-doped Bi2O2CO3 nanoplates were prepared using a solvothermal method.•Fe doping in Bi2O2CO3 was found to greatly decrease the corresponding band gap energy.•The photocatalytic activity of Fe-doped Bi2O2CO3 was significantly enhanced in the photocatalytic degradation of RhB. In this study, Fe-doped Bi2O2CO3 nanoplates were fabricated using a facile solvothermal approach. The successful substitution of Bi3+ by Fe3+ was identified by a shift in the (010) diffraction peak of Bi2O2CO3 at 2θ = 30.2°. A controllable amount of Fe doping in Bi2O2CO3 was utilized to gradually tailor the band gap energy from 3.39 eV to 2.68 eV, resulting in the absorption edge switched from ultraviolet light to visible-light region. Compared to the pure Bi2O2CO3, Fe-doped Bi2O2CO3 nanoplates exhibited an enhanced visible-light photocatalytic activity. With the gradual increase of Fe dopant amount, the photocatlytic activity of Fe-doped Bi2O2CO3 increased initially, and then slightly decreased. Further reactive species trapping experiments demonstrated that holes (h+) and superoxide anion radicals (O2−) played important roles in the photocatalytic oxidation.